EDEUS, a Real-Life Study on the Users of Phosphodiesterase Type 5 Inhibitors: Prevalence, Perceptions, and Health Care-Seeking Behavior Among European Men With a Focus on 2nd-Generation Avanafil - Giovanni Corona, MD, PhD; Mario Maggi, MD, PhD; Emmanuele A. Jannini, MD (Sexual Medicine, 2018)
Introduction: Erectile dysfunction (ED) is a multidimensional disorder with an estimated prevalence of 1% to 10% in men younger than 40 years and up to 100% in men in their 70s and 80s. Aim: To evaluate the real-life characteristics and unmet needs of men with ED, its impact on well-being, and treatment rates across Europe. Methods: Adult men in Belgium, France, Germany, Italy, Poland, Portugal, and Spain were invited to participate in the survey. Men who did not use at least a drug for sexual health in the past 3 months, had cancer or spinal cord injuries, and/or underwent non–nerve-sparing radical prostatectomy were excluded. Main Outcome Measures: The 15-item International Index of Erectile Function (IIEF-15) with study-specific, self-constructed questions was used. Results: Overall, 940 subjects (age = 46.2 ± 13.4 years) were considered. Subjects (n = 778) using on-demand phosphodiesterase type 5 inhibitors (PDE5is) were designated “performers” (60%) without a formal ED diagnosis or “patients” with a medical diagnosis. Patients were older than performers, with more self-reported comorbidities; patients used a higher PDE5i dosage and purchased it from official pharmacies more often than performers did. Of avanafil users (n = 39), no differences in total IIEF or subdomain scores were observed after adjusting for confounders. However, avanafil users less often declared its use without an ED diagnosis and a physician prescription. Overall, the latter condition was associated with higher PDE5i-related satisfaction. Conclusion: The survey shows 2 different attitudes toward ED and PDE5i use: for recreational use and without a medical prescription or with a formal diagnosis and medical prescription. Avanafil, a 2nd-generation PDE5i with a good balance between efficacy and tolerability profile, is more frequently prescribed by doctors than self-prescribed compared with other PDE5is. Because the major challenge is to decrease the high dropout of 1st-generation PDE5is, further studies will be needed to clarify this topic. Corona G, Maggi M, Jannini EA. EDEUS, a Real-Life Study on the Users of Phosphodiesterase Type 5 Inhibitors: Prevalence, Perceptions, and Health Care-Seeking Behavior Among European Men With a Focus on 2nd-Generation Avanafil. Sex Med 2018;6:15–23.